How might micro-credentials influence institutions and empower learners in higher education?. Issue 1 (2nd January 2023) - Pirkkalainen, Henri; Sood, Ira; Padron Napoles, Carmen; Kukkonen, Arttu; Camilleri, Anthony
ABSTRACT: Background: Micro-credentials are increasingly considered a key mechanism through which to empower learners by enabling flexible upskilling and reskilling. Despite their apparent importance for higher education institutions (HEIs) and learners, empirical research is limited. More needs to be understood, particularly about the ways in which micro-credentials can shape institutional practice and provide benefits to learners. Purpose: Using a foresight approach, this study sets out to explore the potential for micro-credential adoption in relation to national and international policy initiatives and rapidly developing technologies. Its intention is to offer findings of interest internationally, particularly to those involved in strategic activities around micro-credentials. Methods: A four-step Delphi study approach was used to explore how micro-credentials may shape higher education (HE) in the next 5–10 years. Educational experts undertook a consensus-building activity utilising workshops and surveys: (1) initial identification of enabling factors (i.e. drivers) and beneficial outcomes (i.e. impacts) of micro-credentials; (2) prioritisation based on importance; (3) identification of enabling factors considered essential for each beneficial outcome and (4) analysis of the extent to which micro-credentials might be accepted in HE, with participants reflecting on the importance of the previously identified enablers and outcomes for alternative scenarios. Findings: The analysis sheds light on three alternative possible futures for micro-credentials. Expert consensus indicated that the potential of micro-credentials lies especially among educational institutions and the networks of institutions innovating beyond, and within, traditional study offerings and programmes. Future wide-scale adoption of micro-credentials was considered unpredictable, due to external factors at the ecosystem level, and beyond institutions' own strategies and control. Conclusion: The findings suggest that, for the successful uptake of micro-credentials, the same benefits do not need to accrue for institutions and learners: a 'one-size-fits-all' approach is not necessary or optimal. In order for the wider-scale influence of micro-credentials to be felt, there is a need for considerable international and national strategy development and implementation to overcome a variety of policy- and technology-related barriers that HEIs cannot influence or tackle on their own.